Sport-specific injuries in children
Sports related injuries are of two types. Macrotrauma occurs as an acute, perhaps dramatic event, like a concussion or spinal cord injury, or a fracture or dislocation. Microtrauma occurs as a repeated injury, usually not noticed initially because the injury is microscopic in magnitude, but where the cumulative trauma leads to pain and in some cases, significant disability. Stress fractures and the so-called overuse syndromes are examples of microtrauma. Any injury can be caused by any sport, but there are injuries that are recognized to be peculiar for a specific sport in a specific age group. The following are some injuries peculiar to certain sports, with suggestions for prevention and treatment.